Antioxidant Activity, Total Phenolic and Flavonoid Content of Honey Bee - Narti Fitriana; Risya Raisyah; Siti Nurbayti; Festy Auliaur Rahmah (Bioscience, 2023)
Honey is a natural product that has many benefits,for living organism. The composition of honey is very diverse and depends on the type of honey and the region of origin. Bioactive compounds in honey including phenolics and flavonoids cause honey to having antioxidant activity. This study aims to identify honey bees, determine the chemical properties of honey based on the parameters of water content, acidity, and reducing sugar, and analyze the antioxidant activity and phenolic and flavonoid content of honey from Bukit Tiga Puluh National Park Riau and Prabumulih South Sumatra. The research using descriptive method were morphological identification of bees, testing parameters of honey bee chemical properties, DPPH antioxidant test to obtain IC50 (Inhibition consenteration) values, total phenolic and flavonoid levels. The identified bees are Apis mellifera (from Riau) and A. dorsata (from Prabumulih). This essay showed that the determination of water content, acidity, reducing sugar, both honeys fulfill SNI 8664:2018 except the reducing sugar of A. dorsata honey bee. A. dorsata honey bee has antioxidant activity higher IC50 value (590 mg/L) than A. mellifera honey (678 mg/L). Total phenolic (TPC) and flavonoid (TFC) of A. mellifera honey were 7.51 mg GAE/g and 0.06 mg QE/g, respectively higher than A. dorsata honey bee (3.35 mg GAE/g and 0.42 mg QE/g).